32x+43-20x=-25+30-45x

Simple and best practice solution for 32x+43-20x=-25+30-45x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 32x+43-20x=-25+30-45x equation:


Simplifying
32x + 43 + -20x = -25 + 30 + -45x

Reorder the terms:
43 + 32x + -20x = -25 + 30 + -45x

Combine like terms: 32x + -20x = 12x
43 + 12x = -25 + 30 + -45x

Combine like terms: -25 + 30 = 5
43 + 12x = 5 + -45x

Solving
43 + 12x = 5 + -45x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '45x' to each side of the equation.
43 + 12x + 45x = 5 + -45x + 45x

Combine like terms: 12x + 45x = 57x
43 + 57x = 5 + -45x + 45x

Combine like terms: -45x + 45x = 0
43 + 57x = 5 + 0
43 + 57x = 5

Add '-43' to each side of the equation.
43 + -43 + 57x = 5 + -43

Combine like terms: 43 + -43 = 0
0 + 57x = 5 + -43
57x = 5 + -43

Combine like terms: 5 + -43 = -38
57x = -38

Divide each side by '57'.
x = -0.6666666667

Simplifying
x = -0.6666666667

See similar equations:

| 6(2x-2)=2x+8 | | 4s+10=2s+(-2) | | 4u-2=5u | | -3q=7+4q | | 2x*2=4 | | 8u=7u-6 | | 49x-50+2=x+3 | | -7y+5y=-10+16 | | 5x(2x-9)-8(2x-9)= | | 4(3x-3)=4x-4 | | 5v+1=4v-3 | | 7w=.875 | | 11-2(3p-10)=5(4-p) | | 3=-2u | | .4285714286y=-2 | | 4000=700x+500 | | 6-2=-9v+v | | 3(2n+5)=3 | | x^3-12=0 | | 20-8=-3z+9z | | 3000=400x+200 | | -9-7(8-3n)=33+7n | | 7x-x=-1-3 | | 2(5x-16)=18 | | b+1=-3-(-2) | | 2000=600x+200 | | 10(2x+1)=70 | | 1000=400*x+200 | | 4x^2-10x=0 | | 2(5x-6)=4 | | 4x^2-19x+53=9x+8 | | 9+8x=3(-10+7x) |

Equations solver categories